Survei Motivasi Masyarakat Mengikuti Senam Aerobik di Sanggar Kabupaten Karanganyar Tahun 2026 - Dina Yuli Puspita; Yudi Karisma Sari; Hartini (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This descriptive quantitative study aimed to analyze the levels of intrinsic and extrinsic motivation among the community participating in aerobic gymnastics at the Karanganyar Regency Studio in 2026, while also determining the most dominant factor. Utilizing a survey technique with a Likert-scale questionnaire instrument, this study involved 30 respondents. Data collection was conducted through the distribution of questionnaires covering internal indicators (health needs, enjoyment, interest, self-satisfaction) and external indicators (environment, peers, facilities, social recognition), which were subsequently processed using descriptive percentage analysis. The results indicated that the community's intrinsic motivation was in the high category at 75.29%, whereas extrinsic motivation fell into the moderate category at 66%. These findings confirm that intrinsic motivation is more dominant in influencing community participation compared to extrinsic factors. In conclusion, internal drive such as the awareness of maintaining health, physical fitness, and fulfilling a healthy lifestyle serves as the primary stimulus for the community to engage in aerobic gymnastics. Meanwhile, external factors such as facilities and group support only act as supporting elements. To maintain and further boost this public interest, gymnastics studios are advised to continuously optimize their service quality and supporting facilities.